2010
DOI: 10.1002/cne.22326
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific antennal sensory system in the ant Camponotus japonicus: Glomerular organizations of antennal lobes

Abstract: Ants have well-developed chemosensory systems for social lives. The goal of our study is to understand the functional organization of the ant chemosensory system based on caste- and sex-specific differences. Here we describe the common and sex-specific glomerular organizations in the primary olfactory center, the antennal lobe of the carpenter ant Camponotus japonicus. Differential labeling of the two antennal nerves revealed distinct glomerular clusters innervated by seven sensory tracts (T1-T7 from ventral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(102 citation statements)
references
References 45 publications
4
93
1
4
Order By: Relevance
“…These data were compared with data from Camponotus floridanus (27,32), because no sex-specific antennal RNAseq data are available for A. vollenweideri. Three-dimensional reconstruction of a clonal raider ant worker antennal lobe from confocal micrograph stacks revealed 493 glomeruli divided into seven clusters defined by diverging input tracts, similar to what has been described in other ants (32,37,38) (Fig. 4A, Table S1, and Fig.…”
Section: Genes In a Clade Of Odorant Receptors Are Expressed In Or Nearsupporting
confidence: 69%
See 1 more Smart Citation
“…These data were compared with data from Camponotus floridanus (27,32), because no sex-specific antennal RNAseq data are available for A. vollenweideri. Three-dimensional reconstruction of a clonal raider ant worker antennal lobe from confocal micrograph stacks revealed 493 glomeruli divided into seven clusters defined by diverging input tracts, similar to what has been described in other ants (32,37,38) (Fig. 4A, Table S1, and Fig.…”
Section: Genes In a Clade Of Odorant Receptors Are Expressed In Or Nearsupporting
confidence: 69%
“…S1). The clonal raider ant male, on the other hand, possessed only 121 glomeruli, even fewer than other ant males (32,38) (Fig. 4B, Table S1, and Fig.…”
Section: Genes In a Clade Of Odorant Receptors Are Expressed In Or Nearmentioning
confidence: 96%
“…With regard to antennal sensory integration, mechanosensory neurons in the antennae are considered to project into the ventral area of flagellar afferents (vfa), which is located in the posterior deutocerebrum in the cricket (Staudacher and Schildberger, 2000). In the carpenter ant, the female-specific basiconic sensilla on the antennae that are responsible for detecting cuticular hydrocarbons project to specific glomeruli in the dorsomedial region of the antennal lobe (Nakanishi et al, 2010). A recent anatomical study indicated that the chemical and tactile information pathways from the antenna are definitely dissociated at least at the level of second-order neurons (Yoritsune and Aonuma, 2012), i.e.…”
Section: Sensory Input To Elicit Aggressive Behaviormentioning
confidence: 99%
“…The antennal basiconic sensilla (SB) of fire ants, Solenopsis invicta are also known to function as contact chemoreceptors [32,33]. Nakanishi et al [15] categorized two types of trichoid sensilla along with the sensilla trichoidea curvata in C. japonicus which does not always respond to stimulation by alarm pheromones [31,34]. Thus, these may have a similar function in M. brunnea also.…”
Section: Discussionmentioning
confidence: 99%